Hydrothermal clay mineral formation in the uraniferous Paleoproterozoic FA Formation, Francevillian basin, Gabon - Ossa Ossa, F.; Hofmann, A.; Vidal, O.; Kramers, J.; Agangi, Andrea; Belyanin, G.; Mayaga-Mikolo, F. (Elsevier, 2014)
The spatial distribution of neoformed clay minerals was investigated in the Paleoproterozoic FA Formation of the Francevillian basin, south-east Gabon, which hosts high-grade U ore deposits associated with the only known occurrence of natural nuclear reactors. Illite appears as the main clay phase in the lower fluvial unit. In the mineralized upper fluvio-deltaic-tidal unit, the clay assemblage is more diversified and commonly characterized by illite, chamosite, berthierine and chamosite/berthierine mixed layers, usually in association with alteration products of U-bearing minerals. The clay mineral assemblage thus potentially constitutes a mineralogical marker for the regional distribution of U ore deposits.Polytype species of the clay phases indicate mineral transformations in an environment characterized by a high fluid/rock ratio. According to crystalline structure, mineral chemistry, thermodynamic modeling and geochronology, clay phases seem to be mainly hygrometer, rather than exclusively a thermometer, and their formation, as well as associated dissolution-precipitation of U-bearing minerals took place between ca. 2040 and 2010. Ma ago, at temperatures of about 240. ±. 30. °C. Using previous burial estimates, this suggests the operation of hydrothermal processes controlled by an external heat source, likely associated with volcanism during deposition of the FD and FE formations. Hydrothermal activity, involving oxidized fluids, would have driven U remobilization and, ultimately, formation of high-grade U ore deposits. The thermal history proposed here allows for a better understanding of the conditions during burial of the sedimentary succession and the origin of its rich U endowment. © 2014 Elsevier B.V.